Higher Risk of Cardiovascular Diseases in Rheumatoid Arthritis Patients Without Methotrexate Treatment - Hloch, Karel; Doseděl, Martin; Duintjer Tebbens, Jurjen; Žaloudková, Lenka; Medková, Helena; Vlček, Jiří; Soukup, Tomáš; Pávek, Petr (Frontiers in Pharmacology, 2021)
Cardiovascular diseases (CVDs) lead to higher morbidity and mortality in rheumatoid arthritis; thus, we aimed to determine whether patients who had discontinued methotrexate treatment before the study enrollment (group MTX 0) were at a higher risk of CVD than patients treated with methotrexate at the time of the data collection (group MTX 1). A retrospective, prospective, observational, cross-sectional study was conducted. A total of 125 patients were enrolled in the study. Patients from the MTX 0 group (n = 35) were not treated with methotrexate for 7.54 (SD ± 4.21) years in average. Medical documentation as well as information taken in patient examinations during regular rheumatologist visits was used to obtain the required data. The composite of any CVD occurred less frequently in patients in the MTX 1 group than in the MTX 0 group (18.8 vs. 40.0%, OR 0.35, 95% CI, 0.15 to 0.83; p = 0.017) with a non-significant trend after adjustment for other treatments, which differed between study groups at the baseline (p = 0.054). Significant difference was found for the reduction of myocardial infarction in the MTX 1 group compared to the MTX 0 group (3.5 vs. 14.3%, OR 0.22, 95% CI, 0.05 to 0.97; p = 0.046). There were 4 deaths (4.7%) in the MTX 1 group as compared with 7 (20.0%) in the MTX 0 group (OR 0.20, 95% CI, 0.05 to 0.73; p = 0.015). Our results demonstrate that patients who discontinued methotrexate treatment are at a significantly higher risk of CVD and all-cause mortality. Based on our findings, we recommend stricter control of CVD in cases of methotrexate discontinuation.